Co3O4 nanoparticles embedded in nitrogen-doped porous carbon dodecahedrons with enhanced electrochemical properties for lithium storage and water splitting. (March 2015) - Hou, Yang; Li, Jianyang; Wen, Zhenhai; Cui, Shumao; Yuan, Chris; Chen, Junhong
Abstract: A novel Co3 O4 /N-doped porous carbon hybrid with dodecahedrons structure was synthesized by a facile, two-step, thermal transformation of a cobalt-based zeolitic imidazolate framework. Well-dispersed Co3 O4 nanoparticles were embedded in nitrogen-doped porous carbon networks, forming a unique nanopolyhedron. When tested as anode material for lithium-ion batteries, the hybrid exhibited superior electrochemical performance, including excellent rate capability of 560 mA h g −1 at 10 A g −1 which is close to 46% of the rate capacity at 100 mA g −1, outstanding cycling stability with 91.7% capacity retention of the second cycle after 110 cycles, and considerably large discharge capacity of 1730 mA h g −1 at 100 mA g −1 . Moreover, the hybrid also showed enhanced electrocatalytic activity for electrochemical oxygen evolution from water splitting. Graphical abstract: A novel Co3 O4 /N-doped porous carbon hybrid with dodecahedrons structure was synthesized by a facile route. Benefiting from a unique nanostructure, the resulting hybrid exhibited excellent electrochemical lithium-storage performance and high electrocatalytic activity for oxygen evolution reaction from water splitting. Highlights: A novel Co3 O4 /N-doped porous carbon hybrid with dodecahedrons structure was successfully fabricated. The hybrid exhibited both superior electrochemical performance as anode material for LIBs and excellent OER catalytic activity as electrocatalyst. The unique nanopolyhedron structure contributed to promising electrochemical performance.